Head First design patterns - Freeman, Eric, 1965-; Robson, Elisabeth; Sierra, Kathy; Bates, Bert (O'Reilly, 2004)
Using research in neurobiology, cognitive science and learning theory, this text loads patterns into your brain in a way that lets you put them to work immediately, makes you better at solving software design problems, and improves your ability to speak the language of patterns with others on your team.